Licensed medicines, off-label use or evidence based: which is most important? - Bonati, Maurizio; Jacqz-Aigrain, Evelyne; Choonara, Imti (BMJ Publishing Group, 2016)
Medicines are licensed for use in humans by regulatory authorities. The concept of licensing is that it helps ensure that medicines are safe, effective and of an adequate quality for regular use.1 Licensing was introduced due to concerns about safety not to ensure that medicines are effective. It was a response to specific examples of drug toxicity, notably the grey baby syndrome in neonates following the use of the antibiotic chloramphenicol and phocomelia in the developing fetus following ingestion of thalidomide by pregnant women.2 Within the UK, the Medicines Act was passed in 1968. The licensing of medicines is both a control on products of public interest as well as an authorisation to sell for pharmaceutical companies. Pharmaceutical companies are only allowed to promote licensed medicines. Prescribers, however, are free to prescribe the most appropriate medicine for their patient. This should be based on the best available scientific evidence. Medicines can be licensed (authorised) by either national regulatory agencies (national route) or the European Medicines Agency